Planned vs. rescue rotational atherectomy in severe coronary calcification: procedural complications and one-year clinical outcomes - Liu, Xiaogang; Wan, Lei; Liu, Yufeng; Gu, Ye; Hu, Liqun (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveCurrent guidelines recommend rotational atherectomy (RA) as a rescue treatment for calcified or fibrotic lesions that cannot be fully expanded before stent implantation. Present study compared the procedural and one-year clinical outcome of planned (pRA) or rescue RA (rRA) for patients undergoing percutaneous coronary intervention with severe coronary stenosis and calcification.MethodsA total of 111 consecutive patients who underwent RA at the Fourth Hospital of Wuhan from July 2021 to June 2023 were enrolled. The general clinical data, coronary artery lesion characteristics, procedural characteristics, complication rate and major cerebral and cardiovascular event [MACCE, cardiac death, acute myocardial infarction (AMI), target vessel revascularization or acute ischemic stroke] rate at one year after procedure were compared between the two groups.ResultsAccording to the timing of initiation of RA, patients were stratified into pRA group (n = 84) or rRA group (n = 27). Baseline clinical characteristics were similar between the two groups. The number of stents implanted was similar in the two groups. The rRA group required more pre—dilation balloons (1.7 ± 0.7 vs. 3.4 ± 0.5, P < 0.001), exhibited a higher rate of coronary artery dissection (29.6% vs. 7.1%, P = 0.02) and consumed a larger volume of contrast (189.8 ± 59 ml vs. 139.9 ± 46 ml, P < 0.001). Additionally, the incidence of contrast—induced nephropathy was significantly greater in the rRA group (29.6% vs. 9.5%, P = 0.01), and the procedure duration was markedly longer in this group compared to the pRA group (91.5 ± 24.3 min vs. 77.9 ± 25.2 min, P < 0.001). Multivariable logistic regression identified rRA as an independent predictor of periprocedural complications (adjusted OR = 2.83; 95% CI:1.01–7.99; P = 0.048). However, 1-year MACCE rates showed no intergroup difference (pRA 3.7% vs. rRA 4.8%; P = 1.00). No significant difference in the secondary endpoints of non-cardiac death, angina pectoris, heart failure, and cardiovascular rehospitalization were observed between the two groups.ConclusionrRA is related with higher procedural complication rates, procedure time, and contrast agent dose compared with pRA, but has similar low MACCE rate as pRA at one year after procedure.